Drawing teaching and special education: interview with Liane Oleques (Revista de Ensino em Artes, Moda e Design, 2024)
The interview addresses the topic of drawing in Early Childhood Education in the context of Special Education with the interviewee Liane Oleques, whose thesis, entitled A possibility of teaching drawing for children with intellectual disabilities, aimed at creating strategies for teaching drawing, application and learning analysis for children with disabilities. Based on Oleques' experience as a researcher and teacher in the area of Special Education, the interview seeks to consider parallels between studiesthat address the characteristics and phases of drawing in Early Childhood Education and the specificities of the development of graphics in childhood in Special Education.The interview also raises questions regarding the methodological approach to teaching drawing in special education based on the interviewee's teaching experience teaching Visual Arts classes at APAE. In this way, we aim to understand how teaching drawing can contribute to the development of students with intellectual disabilities. Furthermore, we address how teaching drawing can be thought of in the school context from the point of view of a methodological approach for students who may present varied forms of learning given the diversity of disabilities, such as sensory, intellectual or multiple.
Keywords: interview; special education; childish drawing